Long-distance restriction mapping of the proximal long arm of human chromosome 21 with Not I linking clones. - Ichikawa, H (1992)
Human chromosome 21 is the smallest of the 22 autosomes and 2 sex chromosomes. Hybridization of the human repetitive sequence Alu to pulsed-field gel-fractionated Not I-digested genomic DNA from a human-mouse hybrid cell line containing chromosome 21 as the sole human component identified chromosome 21 Not I restriction fragments. A Not I restriction map of regions of the chromosome was constructed, by identifying neighboring Alu bands with Not I linking clones. This approach simplifies the task of physical mapping and avoids ambiguities in Not I fragment assignments that arise from gel-to-gel mobility variations. A contiguous map was constructed with six Not I linking clones that covers at least the proximal one-third of the long arm of chromosome 21 and spans 20 megabases. A more detailed restriction map revealed 11 likely CpG islands in this region and localized 11 additional DNA markers.